Determinan Pemilihan Penggunaan Metode Kontrasepsi Jangka Panjang (MKJP) di Puskesmas Sungai Jingah - M. Bahrul Ilmi; Nurul Indah Qariati; Rakhmi Hidayati (Jurnal Akademika Baiturrahim Jambi, 2021)
One of the strategies of the program implementation Plan is listed in its own KB construction of medium-term national (RPJMN) in 2015-2019 is a declining rate of population growth (LPP), decreasing the total birth rate (TFR) per WUS, increasing the use of contraception, decreased needs air-KB which is not met, the declining birth rate in teenagers ages 15-19 years, and decreased unwanted pregnancy of WUS (15-49 years). The scope of use of MKJP (Long-term Contraceptive Methods) is still low and poorly chosen  by  Couples  of  fertile  Age  (PUS)  that  only  amounted  to  9,3%  compared  with  hormonal contraception that is amounted to 88,5%. The purpose of this research is to know the use of determinant Long-term Contraceptive Methods (MKJP) in the Puskesmas Sungai Jingah 2019. This research method using analytic survey with the use of cross sectional. The population is mothers who do visit KB acceptors from January to March 2019 totaled 237 acceptors. The sample in this research is the 70 respondents. Research instrument this is questionnaire with question form and interview. Data analysis with statistical tests test chi square. The desired confidence level is 90% (a = 0,1). Research results showed the use of electoral parity with MKJP (p = 0,488), and support her husband with the use of MKJP (p = 0,003), statistically parity has no relationship with the use of Long-term Contraceptive   Methods (MKJP). While the   husband support   the   selection   of   Long-term use   of Contraceptive Methods (MKJP). Advice for mom user KB is expected to play an active role in the efforts of the use of contraceptives, particularly long -term contraception